2020
DOI: 10.1021/acs.jced.0c00090
|View full text |Cite
|
Sign up to set email alerts
|

Density and Volumetric Behavior of Binary CO2 + n-Decane and Ternary CO2 + n-Decane + Naphthalene Systems at High Pressure and High Temperature

Abstract: Densities of the carbon dioxide + n-decane binary system and carbon dioxide + n-decane + naphthalene ternary system have been measured up to 130 and 100 MPa, respectively, by using a vibrating tube densitometer. The measurements covered the molar compositions of CO2 of 0.1182, 0.3050, 0.6271, and 0.9539 for the first system, at temperatures from 318.15 to 358.15 K. While for the ternary mixtures, the measurements were performed for four compositions: high alkane, high aromatic, high CO2, and one equimolar cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…These results indicate that the addition of CO 2 , above a certain molar composition, reaches a minimal difference regardless of decalin isomers studied ( cis -decalin or trans -decalin), i.e., structural isomerism has a minimal influence on the ternary system intermolecular interactions, and the CO 2 composition dominates the volumetric behavior. This is similar to the results obtained for the ternary system CO 2 + n -decane + naphthalene, as previously published . In the same way, for high- n -decane content mixtures, density data are almost the same for cis -decalin and trans -decalin, especially at pressure below 20 MPa.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…These results indicate that the addition of CO 2 , above a certain molar composition, reaches a minimal difference regardless of decalin isomers studied ( cis -decalin or trans -decalin), i.e., structural isomerism has a minimal influence on the ternary system intermolecular interactions, and the CO 2 composition dominates the volumetric behavior. This is similar to the results obtained for the ternary system CO 2 + n -decane + naphthalene, as previously published . In the same way, for high- n -decane content mixtures, density data are almost the same for cis -decalin and trans -decalin, especially at pressure below 20 MPa.…”
Section: Resultssupporting
confidence: 91%
“…The gas was injected at a constant pressure (10 MPa) at room temperature (298.15 K). A more detailed description could be found elsewhere . Finally, the mixture prepared has been pressurized until 50 MPa to reach a liquid-phase region.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their study reported the density of this mixture at temperatures from (293 to 318) K and pressure up to 100 MPa. Furthermore, the availability of density data for ternary or multicomponent mixtures comprising alkanes with dissolved CO 2 is even more restrictive. …”
Section: Introductionmentioning
confidence: 99%